Seeing flowers : discover the hidden life of flowers - Dunn Chace, Teri (Timber Press, 2013)
Seeing Flowers is a visual feast that gloriously highlights 343 popular garden flowers. Using a unique photo process that includes stitching together large macro photographs, Robert Llewellyn reveals details that few have ever seen: the amazing architecture of stamens and pistils; the subtle shadings on a petal; the secret recesses of nectar tubes. Teri Dunn Chace's lyrical and illuminating essays complement these images and offer insights on each flower, by exploring its distinguishing characteristics and sharing fascinating tidbits, tales, and lore. Together, Llewellyn and Chace give the reader a deeper appreciation of how and why flowers have become so deeply embedded in human culture. Whether you're a nature lover, a gardener, a photography buff, or someone who simply responds to the timeless beauty and variety of the floral world, Seeing Flowers will be a source of enduring delight.